Practitioner Profile: An Interview with Anne Brennan Malec, Ph.D. - Anne Brennan Malec (Journal of Financial Therapy, 2016)
Dr. Anne Brennan Malec is the founder and managing partner of Symmetry Counseling, a counseling, coaching, and psychotherapy group practice located in downtown Chicago. She has been the driving force behind Symmetry Counseling’s success – what started in 2011 with six offices and five counselors now houses over 25 clinicians.
Keywords: practitioner profile; financial therapy; psychotherapy